Bilocular Stafne Bone Defect above And Below the Inferior Alveolar Canal Assessed by Cone Beam Computed Tomography: A Case Report - Mahrokh Imanimoghaddam; Mansoore Darijani; Maryam Keshavarzi (Mashhad University of Medical Sciences, 2015)
Stafne bone defect is a bone depression containing salivary gland or fatty soft tissue on the lingual surface of the mandible. The most common location is within the submandibular gland fossa and often close to the inferior border of the mandible. This defect is asymptomatic and generally discovered only incidentally during radiographic examination of the area. Stafne bone defect appears as a well-defined, corticated, unilocular radiolucency below the mandibular canal. Although it is not uncommon for this defect to appear as a round or ovoid radiolucency, it is rarely seen as a multilocular radiolucency. This report presents a case of a developmental salivary gland defect with multilocular radiolucency above the inferior alveolar canal in a male patient